Climate change-related disasters & the health of LGBTQ+ populations - Samuel Mann; Tara McKay; Gilbert Gonzales (Elsevier, 2024)
Climate change may widen pre-existing health disparities in the lesbian, gay, bisexual, transgender, and queer (LGBTQ+) populations. We argue that LGBTQ+ communities will have more exposure to climate change related disasters, be more susceptible to the adverse impacts of climate change and will have fewer resources to recover from climate disasters. Scholars, practitioners, policymakers, and climatologists need to carefully consider the potential for disparate effects of climate change disasters on the health of LGBTQ+ people. Legislative action protecting LGBTQ+ populations from discrimination, more LGBTQ+ inclusive data collection efforts, and LGBTQ+ sensitivity trainings for disaster relief providers are needed now to ameliorate climate change-related LGBTQ+ health disparities.